APPLICATION OF DIGITTAL TECHNOLOGIES IN PERFORMANCE APPRAISAL - M. Geshkov (Trakia Journal of Sciences)
Performance appraisal is one of the most important parts in human resource management. Perormance appraisals are used when taking impornat decisions regarding employee’s work conditions, including promotions, termination, and rewards. Developmental uses of appraisal, which are geared toward improving employees’ performance and strengthening their job skills, include providing feedback, counseling employees on effective work behaviors, and offering them training and other learning opportunities. If done effectively, performance appraisal can be the key to developing employees and improving their performance. How do modern digital technologies apply to the process of performance appraisal? To answer this question is the purpose of our report. It will be organized as follows: Introduction, Chapter I – Measuring Performance, Chapter II - Application of Modern Digital Technologies in Conducting Performance Appraisal, Conclusion.